Significant genetic gains in grain yield delivered by breeding research: A constant flow of high-yielding, disease-resistant germplasm provided to National Agricultural Research System partners - CGIAR Research Program on Wheat (2020)
The CGIAR Research Program on Wheat (WHEAT) bread wheat breeding program at CIMMYT delivered significant genetic gains to National Agricultural Research System (NARS) partners by developing high-yielding, disease-resistant wheat germplasm. Analysis of historical data showed grain yield gains of 46.6 (irrigated), 57.7 (drought), 65.1 (high rainfall) kg/ha/yea, or 0.5-1% p.a. On-station trials of selected varieties/germplasm delivered similar estimates. These genetic gains in grain yield impact an estimated 61 million hectares of the 215 million hectares of the global wheat area.